Preliminary findings on the use of intravascular ultrasound in the assessment of pediatric pulmonary vein stenosis. Issue 3 (16th September 2020) - Callahan, Ryan; Jenkins, Kathy J.; Gauthier, Zachary; Gauvreau, Kimberlee; Porras, Diego
Abstract: Objective: Determine the feasibility of performing intravascular ultrasound (IVUS) in pediatric pulmonary vein stenosis (PVS) and investigate whether IVUS can delineate the mechanism of PVS. Background: The use of IVUS in pediatric patients with PVS has not been reported. Methods: Retrospective, single center, cohort analysis of all patients who underwent IVUS of pulmonary veins from August 2016 to December 2019. Results: IVUS was performed on 81 pulmonary veins in 50 pediatric patients (median age = 1.7 years [0.9, 3.1], median weight = 8.6 kg [7.3, 11.8]). All veins accepted the IVUS catheter (.014 or .018), with adequate visualization in 88% (71/81) of imaged veins, and improvement in visualization in the more recent period (23/24; 96%). Veins were categorized as having presumed intimal thickening (PIT) with luminal narrowing ( n = 36), ostial narrowing without PIT ( n = 14), distortion/compression ( n = 6), normal ( n = 2), and stent with ( n = 9) or without in‐stent stenosis ( n = 4). In veins with at least 6 months of follow up, (re)intervention occurred more commonly in veins with PIT (14/19; 74%) versus veins without PIT (3/13; 23%; p = 0.01). There were no IVUS related adverse events. Conclusion: IVUS can be used safely in pediatric patients and can reliably demonstrate vein lumen and wall architecture. With further refinement, IVUS has the potential to differentiate intimal neo‐proliferation from other mechanisms of obstruction. The exact role of IVUS in the assessment of pediatric PVS is yet to be determined.